Escenas de la vida rural - Oz, Amos; García Lozano, Raquel (Madrid : Siruela, 2012)
Strange things are happening in Tel Ilan, a century-old pioneer village. A disgruntled retired politician complains to his daughter that he hears the sound of digging at night. Could it be their tenant, that young Arab? But then the young Arab hears the diggings sounds, too. And where has the mayor's wife gone, vanished without trace, her note saying "Don't worry about me"?
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Villages -- Israel -- Fiction; Electronic books